Photochemically-Mediated Inflammation and Cross-Presentation of Mycobacterium bovis BCG Proteins Stimulates Strong CD4 and CD8 T-Cell Responses in Mice - Waeckerle-Men, Ying; Kotkowska, Zuzanna K.; Bono, Géraldine; Duda, Agathe; Kolm, Isabel; Varypataki, Eleni M.; Amstutz, Beat; Meuli, Michael; Høgset, Anders; Kündig, Thomas M.; Halin, Cornelia; Sander, Peter; et al. (Frontiers in Immunology, 2022)
Conventional vaccines are very efficient in the prevention of bacterial infections caused by extracellular pathogens due to effective stimulation of pathogen-specific antibodies. In contrast, considering that intracellular surveillance by antibodies is not possible, they are typically less effective in preventing or treating infections caused by intracellular pathogens such as Mycobacterium tuberculosis. The objective of the current study was to use so-called photochemical internalization (PCI) to deliver a live bacterial vaccine to the cytosol of antigen-presenting cells (APCs) for the purpose of stimulating major histocompatibility complex (MHC) I-restricted CD8 T-cell responses. For this purpose, Mycobacterium bovis BCG (BCG) was combined with the photosensitiser tetraphenyl chlorine disulfonate (TPCS2a) and injected intradermally into mice. TPCS2a was then activated by illumination of the injection site with light of defined energy. Antigen-specific CD4 and CD8 T-cell responses were monitored in blood, spleen, and lymph nodes at different time points thereafter using flow cytometry, ELISA and ELISPOT. Finally, APCs were infected and PCI-treated in vitro for analysis of their activation of T cells in vitro or in vivo after autologous vaccination of mice. Combination of BCG with PCI induced stronger BCG-specific CD4 and CD8 T-cell responses than treatment with BCG only or with BCG and TPCS2a without light. The overall T-cell responses were multifunctional as characterised by the production of IFN-γ, TNF-α, IL-2 and IL-17. Importantly, PCI induced cross-presentation of BCG proteins for stimulation of antigen-specific CD8 T-cells that were particularly producing IFN-γ and TNF-α. PCI further facilitated antigen presentation by causing up-regulation of MHC and co-stimulatory proteins on the surface of APCs as well as their production of TNF-α and IL-1β in vivo. Furthermore, PCI-based vaccination also caused local inflammation at the site of vaccination, showing strong infiltration of immune cells, which could contribute to the stimulation of antigen-specific immune responses. This study is the first to demonstrate that a live microbial vaccine can be combined with a photochemical compound and light for cross presentation of antigens to CD8 T cells. Moreover, the results revealed that PCI treatment strongly improved the immunogenicity of M. bovis BCG.